2011
DOI: 10.1167/11.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Eye guidance in natural vision: Reinterpreting salience

Abstract: Models of gaze allocation in complex scenes are derived mainly from studies of static picture viewing. The dominant framework to emerge has been image salience, where properties of the stimulus play a crucial role in guiding the eyes. However, salience-based schemes are poor at accounting for many aspects of picture viewing and can fail dramatically in the context of natural task performance. These failures have led to the development of new models of gaze allocation in scene viewing that address a number of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
630
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 667 publications
(661 citation statements)
references
References 154 publications
(218 reference statements)
30
630
1
Order By: Relevance
“…This is problematic for the many studies that wish to make conclusions about real world attention from static scene scanning, and it validates a central claim of Tatler et al, (2011) who criticised the picture-viewing paradigm. This key finding also differs from t 'Hart et al, (2009) who found that fixations in static frames (and particularly in continuous movies) could predict gaze in the real world better than spatial biases alone.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This is problematic for the many studies that wish to make conclusions about real world attention from static scene scanning, and it validates a central claim of Tatler et al, (2011) who criticised the picture-viewing paradigm. This key finding also differs from t 'Hart et al, (2009) who found that fixations in static frames (and particularly in continuous movies) could predict gaze in the real world better than spatial biases alone.…”
Section: Discussionmentioning
confidence: 93%
“…And one could do even -28-better than that by including where the eye is usually positioned in the head, and not being concerned at all about the content of any of the scenes. We began our study by discussing the work of Tatler et al (2011) who provided the sobering warning that looking behaviour in computer images may not be especially predictive of looking behaviour in real everyday life. The present study provides a test of that proposal and validates it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Area Under the Curve was used for this purpose in which the saliency map is converted to binary image and then the AUC is calculated and compared to the AUC extracted from the ground truth data (Lin, et al, 2013) (Gide & Karam, 2012), (Zhao & Koch, 2011), (Erdem & Erdem, 2013), and (Kim & Milanfar, 2013). Tatler supported the idea of empirical evaluation of the saliency since they were interested more in mimicking the natural behaviour of the humans' eyes (Tatler, et al, 2011). Precision and Recall, is another method was used by many publications such as (Fang, et al, 2012), (Stöttinger , et al, 2009), (Liu, et al, 2011), (Achanta, et al, 2009), and (Anon., 2013) to evaluate the saliency algorithms.…”
Section: Saliency Evaluationmentioning
confidence: 99%